Bone regeneration by bone morphogenetic protein-2 from porous beads with leaf-stacked structure for critical-sized femur defect model in dogs. (May 2020) - Hong, Sung Jin; Oh, Se Heang; Lee, Sung Lim; Kim, Na-Hyun; Choe, Yong Ho; Yim, Hyeong Jun; Lee, Jae-Hoon
The objective of this study was to investigate whether porous beads with a leaf-stacked scaffold loaded with bone morphogenetic protein-2, with sustained release for up to four weeks, were beneficial to a dog model of critical long bone defects and capable of promoting bone regeneration without side effects. Critical long bone defects were created in the femoral diaphyses of 21 dogs. Each critical defect was fixed with an intramedullary pin and an universal locking plate. Leaf-stacked scaffold beads were implanted into the defect, which was covered with a membrane. Nineteen samples were evaluated 4, 8, and 12 weeks after surgery using simple radiographs, serum chemistry measurements, histological staining, and gene expression analysis. Sustained bone morphogenetic protein-2 release from the leaf-stacked scaffold continued for four weeks and consistently affected the expression of early and late osteogenesis factors. The results suggest that sustained bone morphogenetic protein-2 release is effective for bone regeneration, with minimal side effects.